Relations Work Ability, Discipline, and Job Satisfaction Work With Employee Performance Sub District Kedungwuni Pekalongan - Artika Bina Perdana; Maesaroh Maesaroh; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2012)
Every organization wants its employees to perform optimally. Theperformance results achieved are a person in carrying out the tasks assigned toemployees based on skills, experience, determination and time. One important aspectin realizing the success of employee performance is its ability of government officialswho work professionally. In addition to increased job satisfaction and workdiscipline. The study aims were to determine the relationship of work ability, jobsatisfaction and work discipline to the performance of district employees KedungwuniPekalongan district.This study uses a design or explanatory research design. The population inthis study were all employees of the District Kedungwuni Pekalongan district,amounting to 55 people. the unit of analysis in the form of an employee. Sampleswere taken by census sampling technique, in which all employees were targetedsampling. Techniques of data analysis using the Kendall rank correlation andKendall rank correlation W.Research findings indicate that there is a significant relationship between theability to work with employee performance, there is a significant relationshipbetween job satisfaction with the performance of employees, there is a significantrelationship between the discipline of working with employee performance, there is asignificant relationship between work ability, job satisfaction and disciplineperformance of work by employees in the District Kedungwuni Pekalongan district.Advice can be given to improve the performance of employees, by making theprocedures or standards of work that can be understood and implemented by allemployees. In addition to increasing the available facilities office supplies. Toimprove labor discipline by priventif approach.